R-CHOP without radiation in frontline management of primary mediastinal B-cell lymphoma. Issue 5 (16th April 2019) - Messmer, Marcus; Tsai, Hua-Ling; Varadhan, Ravi; Swinnen, Lode J.; Jones, Richard J.; Ambinder, Richard F.; Shanbhag, Satish P.; Borowitz, Michael J.; Wagner-Johnston, Nina
Abstract: Prior to the introduction of rituximab, primary mediastinal B-cell lymphoma (PMBCL) had high rates of treatment failure with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP), prompting the use of consolidative mediastinal radiation or more intensive chemotherapy regimens. Cure rates improved dramatically with rituximab, but mediastinal radiation was still commonly employed with R-CHOP. We performed a retrospective review of patients treated with R-CHOP alone without radiation for PMBCL. Of 43 patients with PMBCL, 16 received R-CHOP alone. High-risk factors included 56% with bulky disease, 75% with elevated LDH, 25% with SVC syndrome, and 13% with stage IV disease. Three-year progression-free survival (PFS) and overall survival (OS) were 93% and 100% respectively. These results suggest that R-CHOP alone has a high cure rate in PMBCL while avoiding the side effects of mediastinal radiation.